Low switched memory B cells are associated with no humoral response after SARS-CoV-2 vaccine boosters in kidney transplant recipients - Seija, Mariana; García-Luna, Joaquin; Rammauro, Florencia; Brugnini, Andreína; Trías, Natalia; Astesiano, Rossana; Santiago, José; Orihuela, Natalia; Zulberti, Catherine; Machado, Danilo; Recalde, Cecilia; Yandián, Federico; et al. (Frontiers in Immunology, 2023)
Introduction The humoral response after SARS-CoV-2 vaccination and boosters in kidney transplant recipients (KTRs) is heterogeneous and depends on immunosuppression status. There is no validated immune measurement associated with serological response in clinical practice. Multicolor flow cytometric immunophenotyping could be useful for measuring immune response. This study aimed to study B- and T-cell compartments through Standardized EuroFlow PID Orientation after SARS-CoV-2 vaccination and their association with IgG SARS-CoV-2 seropositivity status after two doses or boosters. Methods We conducted a multicenter prospective study to evaluate humoral response after SARS-CoV-2 vaccination in KTRs. Heterologous regimen: two doses of inactivated SARS-CoV-2 and two boosters of BNT162b2 mRNA (n=75). Homologous vaccination: two doses of BNT162b2 mRNA and one BNT162b2 mRNA booster (n=13). Booster doses were administrated to KTRs without taking into account their IgG SARS-CoV-2 seropositivity status. Peripheral blood samples were collected 30 days after the second dose and after the last heterologous or homologous booster. A standardized EuroFlow PID Orientation Tube (PIDOT) and a supervised automated analysis were used for immune monitoring cellular subsets after boosters. Results A total of 88 KTRs were included and divided into three groups according to the time of the first detected IgG SARS-CoV-2 seropositivity: non-responders (NRs, n=23), booster responders (BRs, n=41), and two-dose responders (2DRs, n=24). The NR group was more frequent on mycophenolate than the responder groups (NRs, 96%; BRs, 80%; 2DRs, 42%; p=0.000). Switched memory B cells in the 2DR group were higher than those in the BR and NR groups (medians of 30, 17, and 10 cells/ul, respectively; p=0.017). Additionally, the absolute count of central memory/terminal memory CD8 T cells was higher in the 2DR group than in the BR and NR groups. (166, 98, and 93 cells/ul, respectively; p=0.041). The rest of the T-cell populations studied did not show a statistical difference. Conclusion switched memory B cells and memory CD8 T-cell populations in peripheral blood were associated with the magnitude of the humoral response after SARS-CoV-2 vaccination. Boosters increased IgG anti-SARS-CoV-2 levels, CM/TM CD8 T cells, and switched MBCs in patients with seropositivity after two doses. Interestingly, no seropositivity after boosters was associated with the use of mycophenolate and a lower number of switched MBCs and CM/TM CD8 T cells in peripheral blood.